Selective breeding improves body weight and egg production in indigenous Tilili chicken in Ethiopia - Kassa, Birhan; Taye, M.; Esatu, Wondmeneh; Kebede, A.; Genetu, G.; Asmare, Z.; Lulie, B.; Jember, Z.; Yismaw, K.; Tesfa, A.; Girma, Mekonnen; Kebede, F.G.; et al. (Taylor and Francis, 2026)
1. This study evaluated body weight and egg production performance of Tilili indigenous chicken from different filial generations as a result of the selective breeding.